The international surface temperature initiative global land surface databank: monthly temperature data release description and methods. (30th June 2014) - Rennie, J. J.; Lawrimore, J. H.; Gleason, B. E.; Thorne, P. W.; Morice, C. P.; Menne, M. J.; Williams, C. N.; de Almeida, W. Gambi; Christy, J.R.; Flannery, M.; Ishihara, M.; Kamiguchi, K.; et al.
<x xml:space="preserve">Abstract</x> Described herein is the first version release of monthly temperature holdings of a new Global Land Surface Meteorological Databank. Organized under the auspices of the International Surface Temperature Initiative (ISTI), an international group of scientists have spent three years collating and merging data from numerous sources to create a merged holding. This release in its recommended form consists of over 30 000 individual station records, some of which extend over the past 300 years. This article describes the sources, the chosen merge methodology, and the resulting databank characteristics. Several variants of the databank have also been released that reflect the structural uncertainty in merging datasets. Variants differ in, for example, the order in which sources are considered and the degree of congruence required in station geolocation for consideration as a merged or unique record. Also described is a version control protocol that will be applied in the event of updates. Future updates are envisaged with the addition of new data sources, and with changes in processing, where public feedback is always welcomed. Major updates, when necessary, will always be accompanied by a new journal paper. This databank release forms the foundation for the construction of new global land surface air temperature analyses by the global research community and their assessment by the ISTI's benchmarking and assessment working group.